2020
DOI: 10.1515/med-2020-0216
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 regulates the growth of fibroblasts and extracellular matrix deposition in pelvic organ prolapse

Abstract: This study was carried out to observe the impact of insulin-like growth factor-1 (IGF-1) on human vaginal fibroblasts (HVFs) in the context of pelvic organ prolapse (POP) and to explore its effects on mitogen-activated protein kinases (MAPK) and nuclear factor-κB (NF-κB) signaling pathways. First, it was found that IGF-1 expression reduced in the vaginal wall tissues derived from POP compared to that in non-POP cases. Then the role of IGF-1 was explored in HVFs and thiazolyl blue tetrazolium bromide (MTT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[23,24] Moreover, the growth and apoptosis of fibroblasts are associated with POP. [25,26] Herein, VWFs were isolated from the vaginal wall tissues of patients with POP and non-POP. We found FZDs are regulators of cell phenotype that are involved in gynecological diseases, such as ovarian cancer, cervical cancer, and polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,24] Moreover, the growth and apoptosis of fibroblasts are associated with POP. [25,26] Herein, VWFs were isolated from the vaginal wall tissues of patients with POP and non-POP. We found FZDs are regulators of cell phenotype that are involved in gynecological diseases, such as ovarian cancer, cervical cancer, and polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23,24 ] Moreover, the growth and apoptosis of fibroblasts are associated with POP. [ 25,26 ] Herein, VWFs were isolated from the vaginal wall tissues of patients with POP and non‐POP. We found VWFs are spindly.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 belongs to the insulin-like growth factor family, which includes insulin-like polypeptides mainly synthesized by the liver. IGF-1 can regulate ECM metabolism and various biological processes, such as cell proliferation, differentiation, and apoptosis ( 40 , 41 ). One study ( 40 ) have shown that IGF-1 levels in vaginal wall tissues were lower in patients with POP than in non-POP controls, and it induced the proliferation of vaginal wall fibroblasts, activated mitogen-activated protein kinase (MAPK) and nuclear factor-κ-gene binding (NF-κB) pathways, promoted the metabolism of type I and III collagen another study ( 42 ) reported that IGF-1 can be used as an inhibitor of apoptosis and it may also stimulate fibroblasts to release ECM molecules, such as polysaccharides and proteins.…”
Section: Igf-1mentioning
confidence: 99%
“…Matrix molecules participate in different signaling pathways and finally control cellular behavior [118]. Their synergistic action with IGF/IGF-IR signaling pathway is involved in cancer's pathogenesis [119][120][121][122]. The interactions are perpetrated in two directions: (i) IGF/IGF-IR regulates sarcoma matrix effector synthesis, structure/organization, and downstream functions; and (ii) sarcoma matrix effectors modulate IGF/IGF-IR pathway restricted signaling.…”
Section: Interplay Between Matrix Effectors and Igf/igf-ir Signaling Regulates Sarcoma Functionsmentioning
confidence: 99%